The influence of practice culture on designed artefacts. Issue 4 (12th May 2016) - Schmidt, Robert; Dainty, Andy
Abstract : Design can be viewed as a complex and on-going social accomplishment, a product of everyday trajectories between a milieu of human and material registers. Seen in this way the design practice serves as an arena for these quotidian activities. We seek to construct a more dynamic picture of architecture by connecting process and product, supplementing a project narrative with one of practice, highlighting the context in which the outcome was created. We address the research question: how does practice culture become intertwined within the designed product? A research model emerged from the review of the literature and evolved as a loose framework to discuss the practices and projects at hand. The research focused on the particular design consideration of adaptability in an effort to direct and ground the study. The research was conducted in two stages –at first a set of interviews were conducted to gain broader insights into the everyday accounts of the practices and secondly, project case studies were selected to further investigate the topic. The narratives reveal the culture of each practice to stress a particular meaning in each context: for Make it is about a beautiful object; for ABA a piece of social infrastructure and; for CGL a business asset. Adaptability finds itself subdued, promoted, compromised and sold as part of the design process and the resultant architecture. Our contribution extends the argument that design is entangled within its socio-cultural surroundings and grounds the culture of practice in the designed artefacts - the way in which a practice handles decision-making contingencies, both endogenous and exogenous forces, will together shape a practice disposition towards design (adaptability). Design that is driven by a strong culture that embeds exogenous influences in the approach tends to provide more adaptable solutions as part of a quest to satisfy long-term, societal concerns.